Smart Services and Customer Expectations - Kenneth Hädecke (Marketing Review St.Gallen, 2021)
Smart services offer the opportunity to permanently stay in touch with customers. The acceptance and adoption of these services depend on customers' individual characteristics and expectations regarding the service. This paper offers a practical categorization of consumers regarding their acceptance of and resistance to smart services in the automotive sector.
Keywords: 650